Access to densely functionalized spirocyclopentenonyl oxindole frameworks via aza- and carbo-Piancatelli rearrangement. Issue 26 (22nd June 2022) - Pramanik, Sourav; Jagadeesh, Chenna; Chatterjee, Ayan; Debnath, Subhas Chandra; Saha, Jaideep
Abstract : The Piancatelli rearrangement on an oxindole-based template enables access to highly functionalized spirooxindole moieties. Abstract : A new strategy for access to spirocyclopentenonyl oxindole frameworks is disclosed. Suitably anchored furfuryl alcohol at C3 of an oxindole was used for the aza-Piancatelli rearrangement, which furnished spirocyclic aminocyclopentenone frameworks with catalytic phosphomolybdic acid. The scope of the transformation was extended to the carbo-Piancatelli rearrangement with various indole derivatives.